PENGARUH KONSENTRASI ASAM SITRAT DAN GULA TERHADAP KARAKTERISTIK JELI TERUNG BELANDA - Sinaga, Bonar Cius; S, Imaculata; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 1 No 1 (2012): Jurnal ITEPA)
This study aimed to determine the concentration of citric acid and sugar to produce jelly tamarillo with the best characteristics. Experimental design used was Randomized Block Design factorial with factors I is the concentration of citric acid that consists of four levels; 1. 0% (w/v) concentration of citric acid from volume of friut juice, 2. 2 % (w/v) concentration of citric acid from volume of fruit juce, 3. 4 % (w/v) concentration of citric acid from volume of fruit juice, 4. 6 % citric acid (w/v) concentration of citric acid from volume of fruit juice and the second factor is the concentration of sugar that consists of three levels such as: 1. the sugar concentration of 45 g in 45 ml of fruit juice, 2. 55 g in 45 ml of fruit juice, 3. 65 g in 45 ml of fruit juice. The treatment was repeated 2 times to obtained 24 units of the experiment and the data were analyzed by analysis of variance. If there is any effect of the treatment, the analysis followed by Duncan's Multiple Range Test. The results showed that the treatment of the interaction between citric acid and sugar very real effect on the moisture content, anthocyanin content, total sugars, and total dissolved solids, while the treatment of acid concentration was highly significant to the degree of acidity (pH) and citric acid and sugar treatment had no effect significant effect on the color, texture, aroma, flavor, overall acceptance. Treatment concentration of citric acid 2% of the volume of fruit juice and sugar 65 g in 45 ml of fruit juice produces jelly with the best characteristics with the criteria: water content of 65.60% w / w, 0.42 mg/100g anthocyanin content, total sugar 31.31%, 2.75 pH, total dissolved solids 17.10 oBrix, color rather like, chewy texture, aroma rather like, flavor rather like and overall acceptance rather like
Keywords: citric acid, sugar, tamarillo, jelly